2015
DOI: 10.1016/j.jpsychires.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Connectome signatures of neurocognitive abnormalities in euthymic bipolar I disorder

Abstract: Objectives Connectomics have allowed researchers to study integrative patterns of neural connectivity in humans. Yet, it is unclear how connectomics may elucidate structure-function relationships in bipolar I disorder (BPI). Expanding on our previous structural connectome study, here we used an overlapping sample with additional psychometric and fMRI data to relate structural connectome properties to both fMRI signals and cognitive performance. Methods 42 subjects completed a neuropsychological (NP) battery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 51 publications
(59 reference statements)
2
18
0
Order By: Relevance
“…56,57 Additionally, several studies have reported that the ventral prefrontal cortex is implicated in the "top-down" regulation of emotional processing in patients with BD. 58,59 The FA reduction in the genu of the corpus callosum in the present study suggests impaired prefrontal interhemispheric connectivity, perhaps leading to neurocognitive deficits in processing speed and working memory, 60 for example, and to emotional dysregulation in patients with BD. Our subgroup analysis of patients with BD I reproduced the finding of decreased FA in the genu of corpus callosum compared with healthy controls, which was consistent with the findings of some previous DTI studies.…”
Section: Discussionmentioning
confidence: 63%
“…56,57 Additionally, several studies have reported that the ventral prefrontal cortex is implicated in the "top-down" regulation of emotional processing in patients with BD. 58,59 The FA reduction in the genu of the corpus callosum in the present study suggests impaired prefrontal interhemispheric connectivity, perhaps leading to neurocognitive deficits in processing speed and working memory, 60 for example, and to emotional dysregulation in patients with BD. Our subgroup analysis of patients with BD I reproduced the finding of decreased FA in the genu of corpus callosum compared with healthy controls, which was consistent with the findings of some previous DTI studies.…”
Section: Discussionmentioning
confidence: 63%
“…Studies investigating the neuropsychological effects of WM abnormalities have consistently demonstrated an association between widespread reductions in FA and slower PS in both HC (32,33) and BD samples (34). Thus, the relationship between reduced right UF FA and slower PS seen in the present study is consistent with an expected neuropsychological outcome of WM pathology.…”
Section: Discussionmentioning
confidence: 99%
“…These structural deficits suggest a potential etiology for frontally-mediated functional deficits seen in prior fMRI studies of bipolar disorder (7) and could explain why IFC functional deficits, in particular, appear trait- rather than state-related. That is, IFC hypoactivation has been reported both in bipolar mania (67, 68) and euthymia (18, 19, 50). Further, prior work shows patients with focal lesions to BA 6 have an increased number of false alarms during a simple Go-NoGo task (65) suggesting that structural abnormalities in this region impair performance.…”
Section: Discussionmentioning
confidence: 99%
“…A well-validated response inhibition task (Go-NoGo) (50) was used to probe brain regions involved in cognitive control, including IFC, other OFC regions (BA 10, 11, 47) and the cingulate (BA 24/32). Task details have been published previously (50) and are illustrated in Figure 1A and presented in the Supplement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation